Collisional line-shape effects in accurate He-perturbed H2 spectra. (January 2022) - Słowiński, Michał; Jóźwiak, Hubert; Gancewski, Maciej; Stankiewicz, Kamil; Stolarczyk, Nikodem; Tan, Yan; Wang, Jin; Liu, An-Wen; Hu, Shui-Ming; Kassi, Samir; Campargue, Alain; Patkowski, Konrad; et al.
Highlights: Two rovibrational transitions in helium-perturbed molecular hydrogen are analysed. Ab initio quantum scattering calculations are utilized to calculate line-shape parameters. Highly-accurate experimental data is used as a reference. Clear collisional-effects distinguish is achieved. Impact of the centrifugal distortion on the line shape is discussed. Abstract: We investigate collisional line-shape effects that are present in highly accurate experimental spectra of the 3-0 S(1) and 2-0 Q(1) molecular hydrogen absorption lines perturbed by helium. We clearly distinguish the influence of six different collisional effects (i.e.: collisional broadening and shift, their speed dependencies and the complex Dicke effect) on the shapes of H 2 lines. We demonstrate that only a very specific combination of these six contributions, determined from our ab initio calculations, gives unprecedentedly good agreement with experimental spectra. If any of the six contributions is neglected, then the experiment-theory comparison deteriorates at least several times. We also analyze the influence of the centrifugal distortion on our ab initio calculations and we demonstrate that the inclusion of this effect slightly improves the agreement with the experimental spectra.